Comparison of direct microscopy and in vitro culture for the detection of Blastocystis hominis among the slum children of Dhaka city - Sultana, Asma; Khanum, Hamida; Barua, Priyanka; Haque, Rashidul (Dhaka University Journal of Biological Sciences, 2015)
Multiple stool samples were collected from 2980 children of Mirpur slum area. The direct microscopy and xenic in vitro culture (XIVC) for 48 hours were done for each of the sample. The prevalence of Blastocystis hominis was found 5.1% in direct microscopy and the highest prevalence was observed in May, 2013 among the children of 9 ‐ 11 years. In culture method, 10.93% children were found positive for the organism. Most affected age group was 9 ‐ 11 years and prevalence was highest in August. In culture, morphological cyst forms were most commonly observed. Data analysis showed that there was a significant association between age group and infection ratio. By comparing the direct microscopy with in vitro culture, it was seen that culture was the most sensitive and reliable diagnostic method for the identification of B. hominis. Dhaka Univ. J. Biol. Sci. 24(2): 169-175, 2015 (July)